The implementation of EFL online learning: how do the non-English department students perceive it? - M. Ali Ghufron (Erudita: Journal of English Language Teaching, 2021)
The COVID-19 outbreak influences nearly all facets of life, including education. This study conducted survey investigations to detect non-English students' views on the implementation of EFL online learning. This study used cross-sectional survey research designs employing questionnaires and interviews as data-gathering devices and procedures. The population of this study was all the first-graders of the Islamic Education Program of a State Institute for Islamic Studies situated in Central Java, Indonesia, in the academic year of 2020/2021. A number of 135 students took part as the sample of this study. The results of the study showed that there are three main phases of EFL online learning. First, at the preparation phase, they had high optimism of EFL online learning. Second, it turned into caution and forbearance at the implementation phase. At last, their optimistic level was increasing at the end (evaluation phase). This study means that it is not simple to retain the enthusiasm and optimism of students through EFL online study, particularly in non-English department classrooms. Teachers should be innovative in delivering instructions for learning, offering learning equipment, and selecting appropriate learning platforms. Teachers should also be able to comprehend pupils' psychological state to prevent boredom in online learning.